Fate of nitrogen in floating-raft aquaponic systems using natural abundance nitrogen isotopic compositions. (November 2017) - Wongkiew, Sumeth; Popp, Brian N.; Kim, Hye-Ji; Khanal, Samir Kumar
Abstract: Nitrogen is a key nutrient for fish and vegetable productions in aquaponic systems. However, the fate of nitrogen in aquaponic systems has not been fully understood, leading to difficulty in optimizing nitrogen use efficiency (NUE) and plant production. In this study, the fate of nitrogen in floating-raft aquaponic systems with two plant species, pak choi ( Brassica rapa L. chinensis ) and lettuce ( Lactuca sativa longifolia cv. Jericho ), and tilapia ( Oreochromis sp.) was evaluated using mass balance and natural abundance nitrogen isotopic compositions. Dissolved oxygen (DO) levels associated with hydraulic loading rate (HLR) were found to positively affect nitrite oxidation rate. Increase in nitrite concentration was observed in recirculating water under low DO levels. Nitrite is an intermediate in the dissimilatory reduction of nitrate to N2 gas. Based on progressive enrichment of 15 N of nitrate with time in the recirculating water, we estimated total nitrogen loss of up to 46.3% via denitrification. Nitrogen loss via denitrification was reduced by 44–56% when the feed-to-plant ratio was decreased by 30%. Results of this study provide better understanding of nitrogen transformations, which could help in designing and operating efficient aquaponic systems. Graphical abstract: Highlights: Nitrogen isotope mass balance was used to investigate fate of nitrogen. Hydraulic loading rate maintained high dissolved oxygen level in aquaponics. Dissolved oxygen levels affected rates of nitrite oxidation and denitrification. Denitrification, enhanced at high feeding rate, contributed to nitrogen loss. Lowering the feed-to-plant ratio reduced nitrogen loss via denitrification.